Molecular interaction study on Gemini surfactant and nanoparticles in wax inhibition of Malaysian crude oil - VijayaKumar, Shamala Devi; Norida, Ridzuan (John Wiley & Sons, 2021)
Wax deposition can cause a slowdown in operation by restricting crude oil flow in the pipeline. Chemical inhibitors interact with the wax molecule in crude oil and prevent wax aggregation. The molecular dynamics (MD) simulation was used to analyze the intermolecular interaction between a wax molecule of n-icosane and a Gemini surfactant 2,5,8,11 tetramethyl 6 dodecyn-5,8 diol ethoxylate (GS) with three distinct nanoparticles: silicon dioxide (SiO2)(NP1), tin oxide (SnO)(NP2), and nickel oxide (Ni2O3)(NP3). The desired structural feature of the radial distribution function (rdf) was analyzed using the COMPASS force field. Weakest intermolecular interaction between n-icosane (highest rdf value of 5.25 Å), indicating high wax solubility, was achieved in the presence of GS/NP3 blend. In addition, GS/NP3 blend gave the strongest van der Waals (vdW) interaction with a hydrogen atom in n-icosane. The presence of the O carbonyl group in both GS and NP3 establishes a higher number of hydrogen bonds. Thus, the GS/NP3 blend acts as the best inhibitor compared to the individual GS and NP3. The simulation analysis on the degree of wax formation reduction using GS/NP3 blend correlated well with cold finger experiment that showed a wax formation reduction of 61.6%.